Assessing Knowledge Regarding Managing Congestive Health Failure Symptoms: Differences in Patient and Professional Scores. (December 2018) - Berrios-Thomas, Saskia; Engel, Rafael; McCall, Janice; Rosen, Daniel
Objective: To assess whether patients with congestive heart failure (CHF) and health coaches agree about patient knowledge of health-enhancing practices related to CHF after ongoing telehealth coaching. Methods: Forty patients with CHF and eligible for both Medicare and Medicaid were recruited from a regional managed care organization for this pilot study. Telecoaching sessions via a health insurance portability and accountability act(HIPAA)-compliant tablet-based platform focused on educational information designed to improve patient self-care. Social workers administered the 13-item Member Confidence Measure at baseline and at 30 and 180 days into the intervention. Patients and social workers provided separate ratings. Results: As expected at baseline, patient and coach scores differed, with patients reporting higher perceived knowledge scores ( P < .01). Contrary to expectation, patient and coach scores did not converge at 30 and 180 days. Patient scores continued to increase at 30 and 180 days, while coaches' scores increased at 30 days, but not at 180 days. Conclusion: Overall, patients continued to overrate their understanding about CHF. A telecoaching platform provides an opportunity to enhance patient's knowledge of their chronic disease and for patients to sustain that knowledge over time. Practice Implications: Addressing a patient's misperception of their knowledge to manage a chronic disease is critical for enhancing well-being. Coaches' scores did increase at 30 days suggesting that telecoaching is effective, but more monitoring may be required to ensure that these gains persist over time.